"I like my baby heir with baby hair and afros": Black majesty and the fault-lines of colonialism. (January 2021) - Willson, Nicole
Abstract: This article interrogates the politics and aesthetics of Black majesty that Meghan Markle and other cultural interlocutors such as Beyoncé Knowles-Carter both inform and embody. At the same time, it probes the cultural-historical significance of Black queenship and its relationship to a tradition of Black insurgency and anticolonial resistance from the Age of Revolution to the present, looking closely at Meghan Markle in conversation with Marie-Louise Christophe, first Queen of Haiti. It nevertheless problematises the proposition that any iteration or interpretation of majesty can truly be considered 'radical' when it so often hinges on capitalist ideals of meritocracy, social inequality and what Paul Gilroy has termed 'bootstraps neoliberalism'. It also considers whether this model of Black majesty presents a robust challenge to the 'interlocking systems' of oppression that bell hooks has constituted as 'imperialist white supremacist capitalist patriarchy'. Above all, it contends that the concept of Black majesty represents a symbolic point of rupture that exposes colonial fault-lines.